Peningkatan Kualitas Pembelajaran dengan Modul Ajar dan Evaluasi Pembelajaran: Wildan Alfani Fitron, Yessi Awalinda Rifki, Yuliatun Nikmah, Zulva Abrori, Nurul Malikah - YULIATUN NIKMAH (https://ejournal.insuriponorogo.ac.id/, 2024)
This research aims to improve the quality of learning by developing teaching modules and innovative learning evaluations. Teaching modules that are systematically and attractively designed are expected to facilitate students' understanding of the subject matter. In addition, varied and competency-oriented learning evaluations are expected to provide constructive feedback for students and teachers. Teachers play an important role in creating effective learning, and teaching modules and learning evaluations are the main tools to achieve this. As systematic learning tools, teaching modules help teachers deliver material in a structured manner and facilitate students to learn independently. On the other hand, learning evaluation serves as a tool to measure the extent to which students understand the material taught and a reflection for teachers in improving their teaching methods. The method used in this research is descriptive qualitative. By integrating these two aspects, educators can create a more productive and responsive learning environment, so that students can achieve their potential optimally. Consistent and sustainable implementation of teaching and evaluation modules will contribute to improving the overall quality of education. However, challenges such as limited resources and integration of technology in the evaluation process still need to be overcome to improve the quality of education overall. keyword: Teaching Module, Learning Evaluation, Integration